The Implication of Xenophobic Violence on Nigeria-South Africa Relations (Journal of International Studies, 2017)
The renewed xenophobic attacks in South Africa on Nigerians and other Africans is an ugly trend that raises serious concern among experts and analysts of foreign relations. The latest scenario in Pretoria has resulted in the loss of innocent lives and valuable properties destroyed by some militant youths in South Africa. According to Nigeria’s Foreign Affairs and Diaspora Advisor, Abike Dabiri-Erewa, the country has lost about 116 nationals due to the unlawful acts of some hoodlums in South Africa. This remains a significant setback and which poses a threat to the external relations of Nigeria and South Africa. The research relies on secondary data, such as journals, books, Internet materials, newspaper and official communications between South Africa and Nigeria. The ugly trend of xenophobic attack has resulted in a cold war between Nigeria and South Africa in their socio-economic and political relationships. However, the paper infers that adequate actions are required to be taken to restore and guarantee peace for the immigrants residing in South Africa. Failure to curb the menace of xenophobic violence in South Africa might degenerate into regional conflict which invariably will affect the relationship between both nations in all ramifications. The research contributes to existing literature on the issue of xenophobic attack and its impact on foreign relations; it also gives insight on the recent xenophobic attack which occurred in 2017 and its impact on Nigeria and South Africa relations.